Maternal betel quid use during pregnancy and child growth: a cohort study from rural Bangladesh - Mohammad Redwanul Islam; Shaki Aktar; Jesmin Pervin; Syed Moshfiqur Rahman; Monjur Rahman; Anisur Rahman; Eva-Charlotte Ekström (Taylor & Francis Group, 2024)
Background Chewing betel quid (BQ) - a preparation commonly containing areca nut and slaked lime wrapped in betel leaf - is entrenched in South Asia. Although BQ consumption during pregnancy has been linked to adverse birth outcomes, its effect on postnatal growth remains largely unexplored. Objective We examined the associations of BQ use during pregnancy with children's height-for-age and body mass index-for-age z-scores (HAZ and BAZ, respectively) and fat and fat-free mass along with sex-based differences in association in rural Bangladesh. Methods With a prospective cohort design, we assessed BQ use among mothers enrolled in the Preterm and Stillbirth Study, Matlab (n = 3140) with a structured questionnaire around early third trimester. Children born to a subset of 614 women (including 134 daily users) were invited to follow-up between October 2021 and January 2022. HAZ and BAZ were calculated from anthropometric assessment, and fat and fat-free mass were estimated using bioelectric impedance. Overall and sex-specific multiple linear regression models were fitted. Results Growth data were available for 501 children (mean age 4.9 years): 43.3% of them were born to non-users, 35.3% to those using prior to or less-than-daily during the survey, and 21.3% to daily users. No statistically significant associations were observed after adjusting for sex, parity, maternal height and education, and household wealth. Conclusions There was no effect of BQ use during pregnancy on postnatal growth in this study. Longitudinal studies following up those born to heavy users beyond childhood are warranted for capturing long-term implications of prenatal BQ exposure.